Analytical model for armature reaction of outer rotor brushless permanent magnet DC motor. Issue 5 (15th March 2018) - Ma, Conggan; Li, Qing; Lu, Haifeng; Liu, Yuewen; Gao, Haibo
Abstract : This study presents an analytical model for calculating the armature reaction magnetic field of outer rotor permanent magnet brushless DC motor (PMBLDCM) in stator stationary coordinate system (SSCS) and rotor rotation coordinate system (RRCS). Firstly, an expression of armature reaction magnetic field of single‐phase winding is deduced, without considering slotting effect. Afterwards, analytical expressions of armature reaction magnetic field in both SSCS and RRCS regardless of slotting effect are obtained using vector addition method. Then complex relative permeances of outer rotor BLPMDCM in SSCS and RRCS are analysed, respectively. Finally, analytical solutions of the armature reaction magnetic field in both SSCS and RRCS are derived, respectively, by multiplying the slotless armature reaction magnetic field and the complex relative magnetic permeance, the self‐ and mutual inductance are calculated by the armature reaction magnetic field. A 46‐ploes‐51‐slots outer rotor BLPMDCM is set as an example, the accuracy of proposed analytical model is verified by the Finite Element Method. Based on this analytical model, the pattern of slotting effect on armature reaction of both outer rotor and internal stator are analysed, respectively, as well as spatial order characteristics and frequency characteristics of armature reaction for outer rotor PMBLDCM in SSCS and in RRCS.